1998
DOI: 10.3181/00379727-218-44303
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocytic Choriomeningitis Virus-Induced Alterations of T Helper-Mediated Responses in Mice Developing Autoimmune Hemolytic Anemia During the Course of Infection

Abstract: The effect of LCMV on CD4+ T lymphocytes was analyzed in C3HeB/FeJ mice after infection with the Docile strain of this virus. Our results indicated that LCMV triggers: i) an inhibition of Th2 lymphocyte differentiation induced by concomitant immunization with a nonviral protein antigen; ii) a depression of T helper-dependent antibody responses elicited by such an immunization; and iii) a CD4+ cell-mediated proliferation of spleen cells leading to increased interleukin-4 and interferon-gamma message expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2000
2000
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…RT-PCR. mRNA was prepared from lysed adherent cells as reported previously (El Azami El Idrissi et al, 1998). CD14 gene expression was measured by RT-PCR with primers described by Liu et al (2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-PCR. mRNA was prepared from lysed adherent cells as reported previously (El Azami El Idrissi et al, 1998). CD14 gene expression was measured by RT-PCR with primers described by Liu et al (2006).…”
Section: Methodsmentioning
confidence: 99%
“…As an internal control, housekeeping hypoxanthine guanine phosphoribosyltransferase (HPRT) gene expression was measured using primers described by Peterson et al (1994). The ratios between CD14 and HPRT expression were calculated and expressed as arbitrary units (El Azami El Idrissi et al, 1998).…”
Section: Methodsmentioning
confidence: 99%
“…An early expression of IFN-c message, analysed as described previously (El Azami El Idrissi et al, 1998), was found in 129/Sv mice, with the strongest message at 2 days after infection (Fig. 1c).…”
mentioning
confidence: 87%
“…T lymphocytes were depleted with GK1.5 anti-CD4 (Dialynas et al, 1983) or 53/6.72 anti-CD8 monoclonal antibody, obtained from ATCC (Ledbetter & Herzenberg, 1979). In vivo efficiency of these antibodies has been extensively reported previously (Coulie et al, 1985;Coutelier, 1991;El Azami El Idrissi et al, 1998). This treatment was not followed by modification in IFN-c levels (Fig.…”
mentioning
confidence: 99%
“…Gene expression was analyzed by RT-PCR as described previously (44). Cells were lysed in Trizol reagent (BRL, Gaithersburg, MD).…”
Section: Rna Extraction and Pcr Amplificationmentioning
confidence: 99%